Application of α2‐adrenergic agonists combined with anesthetics and their implication in pulmonary intravascular macrophages‐insulted pulmonary edema and hypoxemia in ruminants. Issue 4 (12th March 2021) - Abouelfetouh, Mahmoud M.; Salah, Eman; Ding, Mingxing; Ding, Yi
Abstract: Alpha2 ‐adrenergic agonists have been implicated in the development of pulmonary edema (PE) and sustained hypoxemia that lead to life‐threatening pulmonary distress in ruminants, especially with sensitive and compromised animals. Recently, there is limited understanding of exact mechanism underlying pulmonary alterations associated with α2 ‐adrenergic agonist administration. Ruminants have a rich population of pulmonary intravascular macrophages (PIMs) in the pulmonary circulation, which may be involved in the development of pulmonary alveolo‐capillary barrier damage. Hence, the central thesis of this review is overviewing the literatures regarding the systemic use of α2 ‐adrenergic agonists in domestic ruminants, focusing on their pulmonary side effects, especially on the influence of PIMs on the lung. At this moment, further studies are needed to provide a clear emphasis and better understanding of the potential role of PIMs in the lung pathophysiology associated with α2 ‐adrenergic agonists. These preliminary studies would be potentially to develop future medications and intervention targets that may be helpful to alleviate or prevent the critical striking pulmonary effects, and thereby improving the safety of α2 ‐agonist application in ruminants.